Three Early Witnesses of the "Dormition Of Mary" in Christian Palestinian Aramaic from the Cairo Genizah (Taylor-Schechter Collection) and the New Finds in St Catherine's Monastery - Müller-Kessler, Christa (Apocrypha, 2018)
In St Catherine's Monastery two early versions of the "Dormition of Mary" (Liber requiei Mariae) in Christian Palestinian Aramaic have surfaced in the form of palimpsest fragments, which are very difficult to decipher, and date from the fifth to sixth centuries. While these two are hidden as underwriting in double palimpsests with Georgian and Greek script above (Sinai, Georgian NF 19), another early palimpsest version is attested in the Taylor-Schechter Collection from the Cairo Genizah, which is overwritten with a rabbinic text Midrash Sifra. This paper proposes a primary edition and translation of these five palimpsests fragments.